2021
DOI: 10.3389/fimmu.2020.592622
|View full text |Cite
|
Sign up to set email alerts
|

Key Components of Inflammasome and Pyroptosis Pathways Are Deficient in Canines and Felines, Possibly Affecting Their Response to SARS-CoV-2 Infection

Abstract: SARS-CoV-2 causes the ongoing COVID-19 pandemic. Natural SARS-COV-2 infection has been detected in dogs, cats and tigers. However, the symptoms in canines and felines were mild. The underlying mechanisms are unknown. Excessive activation of inflammasome pathways can trigger cytokine storm and severe damage to host. In current study, we performed a comparative genomics study of key components of inflammasome and pyroptosis pathways in dogs, cats and tigers. Cats and tigers do not have AIM2 and NLRP1. Dogs do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
2
18
0
1
Order By: Relevance
“…Accordingly, only mild-to-moderate pathological changes such as interstitial pneumonia and bronchiolitis were detected in the respiratory tract of experimentally infected cats [ 19 , 28 ], whereas severe pathological alterations including necrotic changes were observed in human patients with lower respiratory tract infections [ 29 , 30 ]. It has been suggested that deficiencies of key components of the inflammasome and pyroptosis pathway are responsible for the mild symptomatology observed in cats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, only mild-to-moderate pathological changes such as interstitial pneumonia and bronchiolitis were detected in the respiratory tract of experimentally infected cats [ 19 , 28 ], whereas severe pathological alterations including necrotic changes were observed in human patients with lower respiratory tract infections [ 29 , 30 ]. It has been suggested that deficiencies of key components of the inflammasome and pyroptosis pathway are responsible for the mild symptomatology observed in cats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSDMB is the most divergent member of the GSDM family. Although it is not present in the mouse and rat genomes, felines (cats and tigers) and canines (dogs) contain a Gsdmb orthologue ( 45 ). As shown in the study, human GSDMB is cleaved by chloroquine down-regulate caspase-1 (CASP1) and granzyme A at D236 and K244, respectively, whereas dogs, cats and tigers do not possess these key residues.…”
Section: Gsdm Gene Family In Humans and Micementioning
confidence: 99%
“…The gene encoding the inflammasome stimulatory protein NLRP3 is conserved in carnivorans ( 15 ). To determine whether NLRP3 is operational in carnivoran cells, we primed canine monocyte-derived macrophages (MDMs) (fig.…”
Section: Resultsmentioning
confidence: 99%